(untitled) (Homoeopathy for All, 2024)
persistent, episodic or limited to specific situations. The symptoms of anxiety are both psychological and physical. Most anxiety is part of a transient adjustment to stressful events: adjustment disorders, other more persistent forms of anxiety. These are characterized by the emotion of anxiety, worrisome thoughts, avoidance behaviors and the somatic symptoms of autonomic arousal. Anxiety disorders are divided into three main subtypes: phobic, paroxysmal (panic) and generalized. The nature and prominence of the somatic symptoms often lead the patient to present initially to medical services. Anxiety may be stress related and phobic anxiety may follow an unpleasant incident. Many patients with anxiety also have depression.